2021
DOI: 10.3390/su13094864
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Negative Effects of Emojis in Facebook Sponsored Ads for Establishing Sustainable Marketing in Social Media

Abstract: Emojis are prevalent in modern social media advertising. Despite this fact, little research can be found on its effects on consumer purchase intentions. This study seeks to examine purchase intentions in the context of Sponsored Ads on Facebook News Feeds, their perceived intrusiveness, and how the added factor of emoji presence can further affect consumer perception in order to suggest a pathway for establishing sustainable marketing strategies. We investigated the effect of emojis on consumers and then the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The main objective of this study is to investigate the multidimensional factors that affect renewable purchase intention. According to the consequences of result of H1, there is a significant direct relationship between social media exposure and purchase intention (Lee et al,. 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this study is to investigate the multidimensional factors that affect renewable purchase intention. According to the consequences of result of H1, there is a significant direct relationship between social media exposure and purchase intention (Lee et al,. 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The participants in their study utilized positive emojis such as “thumb up” or “smiling face” to express support for their peers. Al-Garaady and Mahyoob (2021) revealed that the EFL learner participants of their study liked to use emojis for communication [ 56 ], but such an application is likely to have negative effects [ 57 , 58 ]; specifically, emojis could negatively affect their writing skills as their standard writing might be sacrificed because of these convenient and emergent communication tools. Liu et al (2021) examined the use of peer feedback in face-to-face and online EFL writing courses; the Chinese EFL learners in their study indicated that emojis can be beneficial in cultivating positive emotions and building rapport among peers [ 59 ].…”
Section: Prior Studies and Development Of The Hypothesesmentioning
confidence: 99%
“…In this article, we propose that appeals matching language style to the ad content would most effectively elicit donations, whereas a mismatch may result in mixed reactions and even controversy. To date, limited research investigating language style has indicated mixed effects on audience perceptions of marketing communications (e.g., Cao, 2019; Gretry et al, 2017; Jahng & Hong, 2017; J. Lee et al, 2021). The present research considers formal language style in a more serious context of charitable appeals (i.e., a context addressing topics like death, disease, poverty, and natural disasters).…”
Section: Introductionmentioning
confidence: 99%
“…To date, limited research investigating language style has indicated mixed effects on audience perceptions of marketing communications (e.g., Cao, 2019;Gretry et al, 2017;Jahng & Hong, 2017; J. Lee et al, 2021). The present research considers formal language style in a more serious context of charitable appeals (i.e., a context addressing topics like death, disease, poverty, and natural disasters).…”
mentioning
confidence: 97%